MENSWAARDIGHEID: TEMA BINNE SUID-AFRIKAANSE GEREFORMEERDE TEOLOGIE? - Smit, Dirk J. (Scriptura, 2007)
For the major part of the twentieth century human dignity has not been a theme in Reformed theology in South Africa. Rather, Reformed theological anthropology was influenced by other philosophical questions and ideological trends. .....